2021
DOI: 10.3390/toxins13110798
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota and Mycotoxin Contamination of Traditional and Industrial Dry-Fermented Sausage Kulen

Abstract: The aim of this study was to identify and compare surface mycobiota of traditional and industrial Croatian dry-fermented sausage Kulen, especially toxicogenic species, and to detect contamination with mycotoxins recognized as the most important for meat products. Identification of mould species was performed by sequence analysis of beta- tubulin and calmodulin gene, while the determination of mycotoxins aflatoxin B1 (AFB1), ochratoxin A (OTA), and cyclopiazonic acid (CPA) was carried out using the LC-MS/MS (li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In the recent study of mycotoxin contamination of the traditional sausage Kulen performed by Lešić et al [ 27 ], OTA concentrations in 2 out of 16 samples exceeded the recommended value of 1 µg/kg in pork meat and products adopted by the Italian Ministry of Health (3.91 and 6.95 µg/kg) [ 37 ]. In that research, in most of the OTA-contaminated samples, no OTA-producing mould was identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the recent study of mycotoxin contamination of the traditional sausage Kulen performed by Lešić et al [ 27 ], OTA concentrations in 2 out of 16 samples exceeded the recommended value of 1 µg/kg in pork meat and products adopted by the Italian Ministry of Health (3.91 and 6.95 µg/kg) [ 37 ]. In that research, in most of the OTA-contaminated samples, no OTA-producing mould was identified.…”
Section: Resultsmentioning
confidence: 99%
“…Although P. commune , a significant CPA producer, is one of the predominant mould species isolated from dry-fermented meat products, CPA concentrations in products of this type are generally unexplored [ 26 , 41 , 42 ]. To the best of our knowledge, data published so far include 1 study of Spanish dry-cured hams, in which CPA concentrations ranged from 36 to 540 µg/kg [ 28 ], and 2 studies of Croatian traditional sausages [ 26 , 27 ], in which CPA was found in 15% and 31% samples, in the concentration range of 2.50–59.80 µg/kg. In comparison with previous research, the results of this study, which included dry-fermented sausages and dry-cured meat products, showed higher CPA concentrations than in the previous two Croatian sausage studies, and slightly lower concentrations than those found in Spanish dry-cured hams.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All isolates were identified according to Pitt and Hocking (2009) and Samson et al (2019). Molecular identification of mould isolates was performed to verify the results of traditional identification methods and was carried out in full accordance with Lešić et al (2021). The obtained sequences were aligned using Lasergene SeqManPro DNASTAR 13 (Madison, Wisconsin, USA).…”
Section: Mould Identificationmentioning
confidence: 99%